2006
DOI: 10.3200/socp.146.6.733-750
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Authoritarianism, Perceived Threat, and Need for Closure or Structure in Predicting Post-9/11 Attitudes and Beliefs

Abstract: The authors examined relationships among authoritarianism, personal need for closure or structure, perceived threat, and post-9/11 attitudes and beliefs. Participants were 159 undergraduate students in the Southeastern United States. The authors collected data 1 week before the U.S.-led invasion of Iraq in March 2003. Correlation and regression analyses revealed that right-wing authoritarianism and social dominance orientation were significant predictors of support for restricting human rights during the U.S.-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
3
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 50 publications
3
53
3
4
Order By: Relevance
“…All items can be found in Appendix in the online supporting information. Fear of terrorism was gauged using five items based on Crowson, DeBacker, and Thoma () (Cronbach’s α = .96, M = 4.09, SD = 1.78). We assessed anger on government with three items adapted from Sinclair and LoCicero () and Skitka, Baumann, and Mullen () (Cronbach’s α = .94, M = 4.99, SD = 1.80).…”
Section: Methodsmentioning
confidence: 99%
“…All items can be found in Appendix in the online supporting information. Fear of terrorism was gauged using five items based on Crowson, DeBacker, and Thoma () (Cronbach’s α = .96, M = 4.09, SD = 1.78). We assessed anger on government with three items adapted from Sinclair and LoCicero () and Skitka, Baumann, and Mullen () (Cronbach’s α = .94, M = 4.99, SD = 1.80).…”
Section: Methodsmentioning
confidence: 99%
“…When individuals perceive that their physical and psychological well-being is threatened, they direct their attention towards sustaining the natural/social environment. Threats cause individuals to take a defensive posture [67]. Thus, it is proposed that:…”
Section: Perception Of Threat To the Natural/social Environmentmentioning
confidence: 99%
“…Studies addressing the former question have tested whether attitudes toward human and civil rights may be better conceived as unidimensional versus multidimensional in nature, with some studies suggesting that these attitudes can be differentiated into domains such as economic, political, equality, and privacy rights (Crowson, ; Diaz‐Veizades et al., ); as well as domains of rights endorsement, commitment, and restriction (McFarland & Matthews, ). Studies addressing the latter question have found that human and civil rights attitudes are predicted by a number of psychological and ideological correlates, including right‐wing authoritarianism and social dominance orientation (Cohrs et al., ; Crowson, DeBacker, & Thoma, , ; McFarland & Matthews, ), universalism values (Cohrs et al., ), moral judgment development (Crowson & DeBacker, 2008b; Crowson, DeBacker, & Thoma, ; McFarland & Matthews, ; Narvaez, Getz, Rest, & Thoma, ), ethnocentrism (McFarland & Matthews, ), political conservatism (Crowson et al., ; McFarland & Matthews, ), and religious fundamentalism (Crowson & Brandes, ; Narvaez et al., ).…”
mentioning
confidence: 99%